Implementation of gas leak detection and security systems in smart homes - Sonya Sasmita Simanjuntak; Mulkan Iskandar Nasution; Nazaruddin Nasution (Indonesian Physics Communication, 2024)
Leakage of liquified petroleum gas (LPG) cylinders or devices is still one of the main causes of fires known for its flammability so that leaks in LPG are at high risk of fire. To overcome this, a tool is made to prevent crime or gas leaks that often occur to homeowners. This research was conducted to find out the security control system for homeowners and overcome if a gas leak occurs. The method used in this tool is the method of designing a tool to detect gas leaks and a security system at home when left by the owner. From the test results of the prototype that has been designed, the error percentage is 1.6% and also in the MQ2 sensor section where the distance conditions and variables used are distance, time and gas source so that if gas is detected, the fan will turn on and an sms message will appear on the smartphone.